A Produção do espaço das pequenas cidades do Seridó Potiguar - Medeiros, Maria Suelly da Silva (2006)
The present research wants to comprehend the small towns process of production situated in the Seridó Potiguar, under a historical perspective. Many were the ways passedthrough and the social agents involved in the organization of this space that is build in the treefold: cattle-breeding/cotton plantation/mining, giving origin to the firstcenters. Through the analysis of demographic, economical and social aspects we elaborate a small towns urban profile, considering the 80 s period until today. Those aspects reveal a town s systems with several characteristics and impossible to be insert in some table of reference. These elements are showed in the concentration of urban equipment in the distribution of economical opportunities and in the social connection that are made in the routine of each place. However, the analysis of production s process and special organization proportinated us an explanation of small towns reality, confirming its importance in the urban system, catching sight that, although the restrict urban functions presented, it confirms its towns character by organizing andadministratingthe life specific community